From Data Silos to Smart Integrations: A Framework for Enterprise-Wide Interoperability Using APIs, HL7, and JSON - Nikitha Edulakanti (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Each industry has enterprise systems that can be totally independent of others, which means the industry has many data silos, which interfere with real-time decision-making, regulatory governance, and cross-functional coordination. This article provides the strategic approach to the realization of enterprise-wide interoperability by matching the modern architecture of APIs with their standardization in the data structure (HL7, JSON, XML, and CDA). The framework is based on practical experience of deployments in healthcare, finance as well as operations, taking into consideration, not just technical integration, but governance, scaling and lifecycle management as well. It proposes the reusability of components; transformation data tools and ownership models of service that aids organizations in moving out of such ad hoc integrations and move towards a controlled strategic interoperability platform. A pilot study is based on a multi-industry assessment of the framework that determines the effects on the time spent delivering integration, the rate of failures, and reuse of components. The results indicate reduction in the delivery time, reductions in the failure rate, and three-fold increment in component reuse. The framework also improved the levels of integration capability maturity by two levels on an average. These results confirm the usefulness of the tool of API-based architecture and a combination with semantic data models and policies on governance. The paper provides practical recommendations to integration architects and solution leads that want to future proof their systems. After all, this effort proves that breaking down data silos and realizing the power of agility and cross-system intelligence is scalable in enterprise environment. DOI: https://doi.org/10.17762/ijisae.v12i17s.7741